Posterior musculofascial reconstruction in robot‐assisted laparoscopic prostatectomy for the treatment of clinically localised prostate cancer: a Cochrane Review. (6th December 2021) - Rosenberg, Joel E.; Jung, Jae Hung; Lee, Hunju; Lee, Solam; Bakker, Caitlin J.; Dahm, Philipp
Abstract : Objectives: To assess the effects of posterior musculofascial reconstruction robot‐assisted laparoscopic prostatectomy (PR‐RALP) compared to no PR during standard RALP (S‐RALP) for the treatment of clinically localised prostate cancer. Patients and Methods: We performed a systematic search with no restrictions including randomised controlled trials (RCTs) comparing variations of PR‐RALP vs S‐RALP for clinically localised prostate cancer. The quality of evidence was assessed on outcome basis according to Grades of Recommendation, Assessment, Development and Evaluation (GRADE) approach. Our search identified 13 records of eight unique RCTs, of which six were published studies, and two were abstract proceedings. There were 1085 randomised patients, of whom 963 completed the trials. All patients had either cT1c or cT2 or cT3a disease. Results: A PR‐RALP may improve urinary continence 1 week after catheter removal compared to no PR (risk ratio [RR] 1.25, 95% confidence interval [CI] 0.90–1.73; I 2  = 42%, five studies, 498 patients, low certainty of evidence [CoE]). A PR‐RALP may have little to no effect on urinary continence 3 months after surgery compared to no PR (RR 0.98, 95% CI 0.84–1.14; I 2  = 67%, six studies, 842 patients, low CoE). A PR‐RALP probably results in little to no difference in serious adverse events compared to no PR (RR 0.75, 95% CI 0.29–1.92; I 2  = 0%, six studies, 835 patients, moderate CoE). Conclusions: This review found evidence that PR‐RALP may improve early continence 1 week after catheter removal but not thereafter. Meanwhile, adverse event rates are probably not impacted and positive surgical margin rates are likely similar. There was no difference in our subgroup analysis for all outcomes with anterior reconstruction technique when combined with PR vs only PR.